Origin and Dynamics of Dissolved Organic Matter in a Mariculture Area Suffering From Summertime Hypoxia and Acidification - Zhang, Yong; Gao, Xuelu; Guo, Weidong; Zhao, Jianmin; Li, Yanfang (Frontiers in Marine Science, 2018)
Based on six cruises from March to September in 2016, we investigated monthly distributions of dissolved organic matter (DOM) and ancillary water chemistry parameters in a mariculture area in the Northern Yellow Sea, where summertime hypoxia and seawater acidification were observed. The most severe oxygen depletion (hypoxia covered approximately one third of the aquaculture area) and the largest pH decrease (8.07 ± 0.05 in surface layer vs. 7.66 ± 0.07 in bottom layer) were revealed in August. Concentration of dissolved organic carbon (DOC) and the absorption properties of chromophoric DOM (CDOM) were used to characterize DOM. Results showed that DOM was mainly originated from marine in situ processes. In March, a DOM pool with the lowest DOC concentration of 2.53 ± 0.28 mgC L-1 and nearly uniform optical characteristics were presented in the well-mixed water column. In August, however, DOC increased to 4.33 ± 0.35 mgC L-1 in the surface layer and 4.10 ± 0.30 mgC L-1 in the bottom layer. Two nonlinear relationships between the absorption coefficient at 355 nm (aCDOM(355)) and the absorption spectral slope over 275–295nm (S275-295) were revealed. According to modelling results, the nonlinear relationships were mostly caused by the conservative mixing of a refractory CDOM pool with a freshly-produced CDOM pool. Apparent oxygen utilization in August was positively related to DOC but not to aCDOM(355) and S275-295, presumably due to multiple sources of CDOM in bottom waters. The absorption properties of CDOM respond largely to varied pH, however, they would be less affected by ocean acidification since the latter process leads to a limited pH decline.